Flexibility of virtual team-based learning in medical education - Jun, Xin L.; Ahmad Hathim A.A.,; Jing, Yi N.; Noor Akmal Shareela, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Team-based Learning (TBL) is a global educational strategy designed to inculcate self-directed and active learning. There is a new breed of students who are exposed to restricted and compromised teaching and learning methods via online platforms amidst this COVID-19 pandemic. Therefore, this innovation aims to explore the application of active learning among undergraduate medical students through virtual TBL. In this pilot study, the concept of genomics technology is introduced virtually through online platforms, Microsoft TeamsTM and Universiti Kebangsaan Malaysia (UKM) Learning Management System (UKMFolioTM), while maintaining the principles of TBL. Emphasis is placed on applying the fundamental knowledge learnt during the preparation phase through team discussions and subsequent pitching presentation. Our study revealed no significant difference (p = 0.404) in the mean score between students who participated in conventional face-to-face TBL sessions and virtual TBL. This suggests that active and self-directed learning can be integrated through virtual means with reproducible excellent results similar to conventional face-to-face TBL. Nonetheless, issues related to Internet stability and insufficient content experts must be addressed for an effective virtual teaching and learning.